Design a simulating lung in 36h or less - Jean Sébastien Buvat; Laurent Faivre; Pierre Romet; Ludovic Vitu; Julio Badie; Fernando Daniel Berdaguer Ferrari; Sylvain Malfroy (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2022)
Background: During the COVID health crisis, intensive care units were quickly overwhelmed and had to call for help. The only solution was to call for this help among nurses, nursing auxiliaries, and physicians that were normally not working in the ICU units (consultations, operating room, medical units). These people needed mechanical ventilation courses before beginning their job in the ICU unit. Simulation appeared to be the best solution because of its safety and educational effectiveness.  Approach: We developed an artificial lung during the 36 hours innovation marathon Crunch Maker Camp 2021. It included three main settings which were lung compliance, airways resistances, and diaphragmatic inspiratory trigger. These parameters seemed to be essential for us in order to simulate the mechanical ventilation characteristics of a COVID lung. The simulator was entirely made of physical components. Evaluation: The team composed of engineers and intensive care medical instructors developed the first proof of concept of the artificial lung. The different controllable modules were able to adjust compliance, and resistance on the respirator, and an inspiratory trigger was efficient. They reflected correctly a normal or a COVID lung, simulating a patient on a ventilator. The simulator was presented to the jury and after deliberation, the teams' work was rewarded with the first innovation prize. Reflection: We designed a controlled simulation for COVID respiratory issues; the artificial lung was rewarded during this innovation marathon Crunch Maker Camp 2021. This allowed us to improve the simulator and we plan to start using this tool during training sessions soon. We will then measure Pedagogic impact, focusing on long-term memorization.